(untitled) (Sains Humanika, 2023)
Minority communities often face economic struggles. It becomes even worse when they are socially marginalized. For their survival, they adopt different methods to overcome it. There are destructive methods and constructive methods. Community-based entrepreneurship that allows for the execution of particular skills has proved to be one suitable constructive method to overcome their struggle. However, most research does not go further to check whether that method can sustain their existence for good. This study is on a particular group of minorities called Biharis, which refers to the people from the state of Bihar, India, residing as a marginalized group inside a particular sector in Dhaka, Bangladesh. To survive, they have adopted a particular crafting skill of making Benarasi Saree. Saree refers to a traditional garment worn by women in South Asia, while Benarasi refers to something related to the city of Benaras in the state of Uttar Pradesh, India. After a couple of generations, who not only helped overcome the economic struggle to some extent but also brought social inclusion, they faced a new struggle that threatened to make them give up that skill. The aim of the study is to find out what they are thinking to overcome this new struggle. The researchers adopted the qualitative method, searching for a grounded theory by collecting data through participant observation. Later, immersive techniques were applied to extract the implicit themes. Findings suggest that even though they have the passion to keep the skills going, they are ready to give them up without prejudice in order to survive, which brings to attention how significant the intervention from the top is if such rare skills develop in marginalized societies and later cease to exist.